Women’s experiences and challenges with tandem breastfeeding: a qualitative study - Gül Öztaş, Hatice; Durmuş, Ayşenur (Informa UK Limited, 2025)
Tandem breastfeeding is defined as the simultaneous breastfeeding of two children of different ages, either during pregnancy or postpartum. Identifying the emotions and difficulties experienced by mothers during the tandem breastfeeding process is crucial in terms of raising awareness. Accordingly, the objective of this study is to investigate the experiences and challenges associated with tandem breastfeeding. This qualitative study was conducted using a phenomenological research design. Data were collected through online face-to-face interviews conducted via Google Meet in Turkiye between January and March of 2024. Snowball sampling was employed to recruit participants. Fourteen mothers who were concurrently breastfeeding two children participated in the study. The researchers conducted in-depth, individual, open-ended interviews to collect data. The participants were asked to complete a personal information form and a semi-structured in-depth interview. Participants were encouraged to share their experiences with tandem breastfeeding and the challenges they faced. Descriptive data regarding the socio-demographic and obstetric characteristics of the mothers were presented as numbers and percentages. Qualitative data were examined using content analysis. A comprehensive analysis of interview data from tandem breastfeeding women identified eight key themes: happiness, enjoyment, guilt, fear, breast problems, fatigue/boredom, sibling jealousy, and social pressure. Among the tandem breastfeeding mothers, 64.2 percent reported positive emotions, while 35.8 percent reported negative emotions. Furthermore, 28.6 percent of the mothers mentioned difficulties related to "breast problems," 21.4 percent to "sibling jealousy," 28.6 percent to "fatigue and boredom," and 21.4 percent to "environmental pressure. It is important to note that tandem breastfeeding mothers reported positive emotions, yet concurrently indicated the presence of various challenges. During this process, tandem breastfeeding mothers require information and support. In this regard, midwives and nurses play a crucial role in supporting tandem breastfeeding mothers, thereby promoting positive emotions, addressing negative emotions and difficulties, and encouraging breastfeeding.
Keywords: Adult; Interviews as Topic; Breast Feeding; Pregnancy; Emotions; Postpartum Period; Humans; Mothers; Female; Qualitative Research